Prediction of Efficacy of Vabicaserin, a 5‐HT2C Agonist, for the Treatment of Schizophrenia Using a Quantitative Systems Pharmacology Model. (23rd April 2014) - Liu, J; Ogden, A; Comery, TA; Spiros, A; Roberts, P; Geerts, H
Abstract : A quantitative systems pharmacology model that combines in vitro /preclinical neurophysiology data, human imaging data, and patient disease information was used to blindly predict steady‐state clinical efficacy of vabicaserin, a 5‐HT2C full agonist, in monotherapy and, subsequently, to assess adjunctive therapy in schizophrenia. The model predicted a concentration‐dependent improvement of positive and negative syndrome scales (PANSS) in schizophrenia monotherapy with vabicaserin. At the exposures of 100 and 200 mg b.i.d., the predicted improvements on PANSS in virtual patient trials were 5.12 (2.20, 8.56) and 6.37 (2.27, 10.40) (mean (95% confidence interval)), respectively, which are comparable to the observed phase IIa results. At the current clinical exposure limit of vabicaserin, the model predicted an 9‐point PANSS improvement in monotherapy, and <4‐point PANSS improvement adjunctive with various antipsychotics, suggesting limited clinical benefit of vabicaserin in schizophrenia treatment. In conclusion, the updated quantitative systems pharmacology model of PANSS informed the clinical development decision of vabicaserin in schizophrenia. CPT Pharmacometrics Syst. Pharmacol . (2014) 3, e111; doi:10.1038/psp.2014.7 ; published online 23 April 2014